New chemotypes as Trypanosoma cruzi triosephosphate isomerase inhibitors: a deeper insight into the mechanism of inhibition. (April 2014) - Alvarez, Guzmán; Martínez, Jennyfer; Aguirre-López, Beatriz; Cabrera, Nallely; Pérez-Díaz, Leticia; Gómez-Puyou, Marietta Tuena de; Gómez-Puyou, Armando; Pérez-Montfort, Ruy; Garat, Beatriz; Merlino, Alicia; González, Mercedes; Cerecetto, Hugo
Abstract Context: Triosephosphate isomerase (TIM) is a ubiquitous enzyme that has been targeted for the discovery of new small molecular weight compounds used against Trypanosoma cruzi, the causative agent of Chagas disease. We have identified phenazine and 1, 2, 6-thiadiazine chemotypes as novel inhibitors of TIM from T. cruzi (TcTIM). Objective: Study the mechanism of TcTIM inhibition by a phenazine derivative and by a 1, 2, 6-thiadiazine derivative. Methods: We performed biochemical and theoretical molecular docking studies to characterize the interaction of the derivatives with wild-type and mutant TcTIM. Results and conclusion: At low micromolar concentrations, the compounds induce highly selective irreversible inactivation of parasitic TIM. The molecular docking simulations indicate that the phenazine derivative likely interferes with the association of the two monomers of the dimeric enzyme by locating at the dimer interface, while 1, 2, 6-thiadiazine could act as an inhibitor binding to a region surrounding Cys-118.